2020
DOI: 10.47197/retos.v0i39.79350
|View full text |Cite
|
Sign up to set email alerts
|

Possibilidades e potencialidades técnico-táticas em diferentes tradicionais jogos/brincadeiras de bola com os pés (Technical-tactics possibilities and potentialities in different traditional ball games played with feet) (Posibilidades y potencialidades

Abstract: Resumo. O estudo tem como objetivo investigar as possibilidades e diferentes potencialidades dos jogos que compõem a cultura tradicional brasileira de brincadeiras de bola com os pés. Participaram do estudo 28 futebolistas, sendo 14 crianças (Grupo 01: 9,7±1,2 anos) e 14 universitários (Grupo 02: 21,1±1,7 anos). Os jogadores participaram de três jogos/brincadeiras de bola com os pés (Rebatida, Bobinho e Artilheiro). O desempenho dos jogadores foi analisado através do software Dvideow®, que registrou as ações t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
(27 reference statements)
0
7
0
8
Order By: Relevance
“…Still, underpinning the quotes in Table 2 , in spite of the other physical engagements, football seems to be the preferable activity for the interviewees. On this note, it has been reported that more than the 11-a-side regulation form of the sport, various other configurations of the game such as Bobinho (i.e., rondo), Rebote (i.e., rebound), and Artilheiro (i.e., striker, top scorer) have composed the traditional culture of playing ball games with the feet (Scaglia et al, 2021 ). In addition, street football, beach soccer, and futsal have been traditionally played within the Brazilian society (Uehara et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Still, underpinning the quotes in Table 2 , in spite of the other physical engagements, football seems to be the preferable activity for the interviewees. On this note, it has been reported that more than the 11-a-side regulation form of the sport, various other configurations of the game such as Bobinho (i.e., rondo), Rebote (i.e., rebound), and Artilheiro (i.e., striker, top scorer) have composed the traditional culture of playing ball games with the feet (Scaglia et al, 2021 ). In addition, street football, beach soccer, and futsal have been traditionally played within the Brazilian society (Uehara et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, only cognitivism and constructivism are recognized as interactionist approaches since they are inherently conducted within the context of play (Scaglia et al, 2014). These two approaches reflect the conditions for the learners to reach their potential in relation to their autonomy in reading the play and making decisions (Scaglia et al, 2021). We also understand that, even if only these two approaches are showing a greater applicability to the play -at the expense…”
Section: Applicability Of Learning Approaches To the Learning Of "Actions In The Play"mentioning
confidence: 86%
“…The characteristics that will make players integrate new content into their "way to play" include awareness and reading of the game (Scaglia et al, 2021). Such characteristics help players recognize the situations of play where the new content, intentions, or advice from the coaches apply.…”
Section: Capabilities Favoring the Non-linear Learning Of The Gamementioning
confidence: 99%
See 2 more Smart Citations